Психолого-педагогическая подготовка как важный компонент профессионального образования студентов технических высших учебных заведений - Чебакова, Юлия Григорьевна (НТУ "ХПИ", 2009)
The author analyzes features of psihologo-pedagogical preparation in a technical higher educational institution. By means of this preparation the student can successfully solve psychological, industrial and other problems in future professional work and create round itself fa¬vorable conditions for work
Keywords: кафедра педагогики и психологии управления социальными системами НТУ "ХПИ"; интегрированная подготовка инженеров; управленческая подготовка